2021
DOI: 10.1002/pro.4153
|View full text |Cite
|
Sign up to set email alerts
|

DichroWeb, a website for calculating protein secondary structure from circular dichroism spectroscopic data

Abstract: Circular dichroism (CD) spectroscopy is a widely‐used method for characterizing the secondary structures of proteins. The well‐established and highly used analysis website, DichroWeb (located at: http://dichroweb.cryst.bbk.ac.uk/html/home.shtml) enables the facile quantitative determination of helix, sheet, and other secondary structure contents of proteins based on their CD spectra. DichroWeb includes a range of reference datasets and algorithms, plus graphical and quantitative methods for determining the qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
203
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 297 publications
(215 citation statements)
references
References 39 publications
4
203
0
8
Order By: Relevance
“…Compared to Tt TF (EDTA), the CD spectrum of Tt TF (Zn 2+ ) showed a smaller magnitude of the mean residue ellipticities for the region from 208 nm to 222 nm (the negative absorption peak of α-helix), indicating that Tt TF (Zn 2+ ) contains less α-helix. The secondary structure content predicted from the CD spectra using Dichroweb [ 23 ] showed that Tt TF (Zn 2+ ) contains a smaller portion of α-helix but contains a larger portion of β-sheet ( Figure 3 B, Table 2 ), indicating the zinc-induced structural changes of Tt TF. CD measurements at different temperature points, 20 °C, 35 °C, 65 °C, and 80 °C, showed essentially the same trend, that the mean residual ellipticity of Tt TF (Zn 2+ ) is less negative than that of Tt TF (EDTA) ( Figure S3 and Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to Tt TF (EDTA), the CD spectrum of Tt TF (Zn 2+ ) showed a smaller magnitude of the mean residue ellipticities for the region from 208 nm to 222 nm (the negative absorption peak of α-helix), indicating that Tt TF (Zn 2+ ) contains less α-helix. The secondary structure content predicted from the CD spectra using Dichroweb [ 23 ] showed that Tt TF (Zn 2+ ) contains a smaller portion of α-helix but contains a larger portion of β-sheet ( Figure 3 B, Table 2 ), indicating the zinc-induced structural changes of Tt TF. CD measurements at different temperature points, 20 °C, 35 °C, 65 °C, and 80 °C, showed essentially the same trend, that the mean residual ellipticity of Tt TF (Zn 2+ ) is less negative than that of Tt TF (EDTA) ( Figure S3 and Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Protein concentration was determined based on the absorbance at 280 nm by UV-vis spectrometer JASCO V-730 (JASCO). The neural network program K2D [ 22 ] was used to analyze the secondary structure content of Tt TF (EDTA) and Tt TF (Zn 2+ ) on Dichroweb web service ( , Accessed date: 14 September 2021 and 8–9 October 2021) [ 23 ]. The goodness-of-fit parameters (scaling factor) for the secondary structure analysis of Tt TF (EDTA) and Tt TF (Zn 2+ ) were set to 0.95–1.05 [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…The parameters were set as follows: scanning range = 190-250 nm, temperature = 25 • C, quartz cell path length = 0.1 cm, band width = 1 nm, scan rate = 50 nm/min, and scanning interval = 0.5 nm. The conformational changes in the secondary structures, including α-helix, β-sheet, β-turn, and random coil, were deduced using the computer program CDPro (http://dichroweb.cryst.bbk.ac.uk/html/process.shtml, accessed on 5 January 2021) [32].…”
Section: Circular Dichroism (Cd) Spectroscopymentioning
confidence: 99%
“…The buffer CD spectrum was then subtracted from the protein spectrum to obtain a true CD spectrum of proteins at each temperature and co-solute concentration. The spectra were fit using the Dichroweb [35] and Bestsel programs [36]. The melting temperature of the system was taken by examining the ellipticity of the spectrum at 222 nm, which corresponds to the absorption minimum due to alpha helical secondary structure of the protein.…”
Section: Steady State Spectroscopymentioning
confidence: 99%